Innovation Efficiency in Automotive Industry: The Case of Turkey - Günay, Gizem; Aldemir, Gökhan; Çebi, Ferhan (Springer International Publishing, 2020)
Innovation activities refer to renewal efforts as products, services or processes and the commercialization of these efforts. In this study, the relationships between the innovation activities and company performance in the automotive industry are examined. The R&D expenditures, the number of employees working in the R&D department, the number of projects carried out, the number of patents, trademarks and design registrations are the variables used in connection with the innovation processes. Efficiency values are obtained by using firm data of research and development activities, which can be described as innovation indicators, and their efficiency is compared in terms of innovation with Data Envelopment Analysis (DEA). Accordingly, suggestions are made the companies to be efficient by data envelopment analysis.